STRATEGI PEMBERDAYAAN USAHA KECIL MENENGAH PADA MASA PANDEMI COVID-19 DI KOTA BANDA ACEH (STUDI KASUS DINAS KOPERASI, UKM DAN PERDAGANGAN KOTA BANDA ACEH) - Jhon Wahidi (Universitas Teuku Umar, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the most impactful businesses due to the Covid-19 pandemic. The city of Banda Aceh, which is the capital of the province of Aceh with a fairly large number of MSME traders and the ever-increasing spread of the Covid-19 virus in Aceh, is an important thing for the government to pay attention to regarding the sustainability of MSMEs in order to survive in the midst of the Covid-19 pandemic. The purpose of this study was to find out what strategies and steps were taken in empowering MSMEs by the Cooperatives, SMEs and Trade Office in Banda Aceh City during the COVID-19 pandemic. This study uses a qualitative descriptive approach. The sampling technique was carried out by Convenience Sampling, the data collection technique used the interview, observation, and documentation methods. data analysis using interactive statistical models. The results showed that the strategies carried out by the Banda Aceh City Cooperatives and Commerce Department in minimizing the impact of the Covid-19 pandemic included: 1) Conducting trainings for business actors, 2) providing technical guidance and training on online product marketing such as e-commerce applications. 3) Business capital assistance either comes from the Central Government in the amount of Rp. 2,400,000, - as well as from the Banda Aceh City Government of Rp. 1,000,000,-. 4) providing assistance for work tools and retrieving business tools for business actors in Banda Aceh City.